CONCEPT OF DIFFERENT SAMPRAPTI OF SANDHIGATA VATA (AYUSHDHARA, 2018)
In Ayurveda, Vata is explained as life and vitality, supporter of the all embodied beings and sustains long life free of disorders. In Ayuvedic texts get a very detailed description about Vata vyadhi. There are three Doshas in our body. In all three Doshas, Vayu is Ayu and Bala, without Vata the other two Doshas have been unable to work. In Tridoshas, Vata and Kapha plays an important role in Sandhigata Vata. Sandhigata Vata is the imbalance or vitiation of Vata and this vitiated Vata disturbes the normal state of the Kapha in all the joints. In all Ayurvedic literatures, Sandhigata Vata explains under Vata Vyadhi. The Nidan told for Vata vyadhi, those are same for Sandhigata Vata because in all Ayurvedic literatures there is no separate explanation about Sandhigata Vata. It has been mentioned in this study by taking different Nidan, different Rupa of Sandhigata Vata are produced.  As by taking Ruksh ahar-vihar, Ruksha guna of Vata increases and Vatapurna druti Sparsh lakshana is produced.So, in this study tabulation of different Nidan and Lakshana by different classics are mentioned and different Samprapti of Sandhigata Vata is trying to mention by flow charts.